Microbes for biobutanol production: examining performance and potential in renewable energy solutions - Chan, Rosamond; Nabila, Devina Syifa; Syamsuri, Rizky Riscahya Pratama; Wan-Mohtar, Wan Abd Al Qadr Imad; Ozturk, Abdullah Bilal; Rossiana, Nia; Doni, Febri (TAYLOR & FRANCIS LTD, 2025)
Emerging as a promising biofuel, biobutanol presents a viable substitute for traditional fossil fuels. Through metabolic processes, microorganisms-particularly those of the Clostridium genus-play a salient role in converting a variety of feedstocks into environmentally benign biobutanol. Prominent biobutanol-producing organisms, such as C. acetobutylicum, exhibit varied butanol yields that are controlled by variables like fermentation conditions and substrate types. This review explores into the many microbial species and fermentation routes that are involved in the synthesis of biobutanol, including acetone-butanol-ethanol (ABE), hexanol-butanol-ethanol (HBE), and isopropanol-butanol-ethanol (IBE). Even though microbial biobutanol synthesis faces a number of obstacles, such as yield limits and substrate restrictions, continued developments in metabolic engineering, sustainable feedstock research, and bioprocess refinement point to a bright future for the technology. All of these developments point to biobutanol playing an important role in creating a more environmentally friendly and sustainable energy landscape.
Keywords: Biobutanol; biofuel; biobutanol-producing microorganisms; biobutanol production performance; renewable energy; fermenta-tion pathways; BUTANOL-ETHANOL FERMENTATION; ACETOBUTYLICUM ATCC 824; CLOSTRIDIUM-ACETOBUTYLICUM; BUTYRIC-ACID; SACCHAROMYCES-CEREVISIAE; BACILLUS-SUBTILIS; ESCHERICHIA-COLI; IBE PRODUCTION; TOLERANCE; STRAIN; Engineering